Community engagement approaches and lessons learned: a case study of the PRECISE pregnancy cohort study in Kenya - Wanje, Onesmus; Koech, Angela; Kinshella, Mai-Lei Woo; Mwashigadi, Grace; Kombo, Alice; Maitha, Grace; Barreh, Nathan; Mistry, Hiten D.; Vidler, Marianne; Craik, Rachel; Volvert, Marie-Laure; von Dadelszen, Peter; et al. (Frontiers in Public Health, 2025)
Community engagement (CE) has been recommended as an important ethical consideration for health research to enhance informed consent and exchange knowledge between researchers and community members. The purpose of this paper is to describe how CE was developed and delivered for the PRECISE prospective pregnancy cohort study in Kenya. PRECISE enrolled pregnant women in antenatal care, followed them up to the postpartum period, and collected data and biological samples to enable the study of placental disorders in sub-Saharan Africa. Initially CE was aimed at informing the community about the study, establishing community-wide acceptance of the research and addressing concerns about biological sample collection to facilitate participation in the study. CE later evolved to be a platform for mutual learning aiming to deepen the community’s understanding of research principles and informed consent and providing a feedback loop to researchers. We engaged diverse stakeholders including health workers and managers, local administrators, religious and traditional leaders, older women, pregnant women, non-pregnant women and men. We utilized a variety of CE approaches and tools adapting to the specific contextual factors at the study sites. Achievements included widespread understanding of informed consent and research principles, clarification of misconceptions, and dispelling of fears regarding biological sample collection. The relationship with the community was strengthened evidenced by frequent inquiries and active participation in CE activities and the research study. For effective CE, we recommend involvement of community members in the CE team and continuous and adaptive CE throughout the study period.